2009
DOI: 10.1007/s12550-009-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium toxins in cereals of integrated and organic cultivation from the Federal State of Brandenburg (Germany) harvested in the years 2000–2007

Abstract: Over a period of 8 years (2000-2007), wheat (n = 407) and rye (n = 510) samples of integrated and organic cultivation in the Federal State of Brandenburg were analyzed by HPLC for the Fusarium toxins deoxynivalenol (DON) and zearalenone (ZEA). In the years 2002 and 2007, the overall contamination level was higher than in the other years. The percentage of DON-positives (>50 µg/kg) varied from 5 to 86%, the median and maximum levels varied from 50 to 380 µg/kg and from 50  to 10,400 µg/kg, respectively. The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Organic cultivation is characterized by the omission of maize as previous crop, traditional tillage, and by selection of relatively Fusarium-resistant cultivars. Furthermore, the ban of plant protectants and other chemicals such as fungicides or growth regulators (retardants) which are applied in integrated cultivation could contribute to the relatively low Fusarium contamination (and thus of the low toxin contents) in organically cultivated cereals (Meier et al, 2000;Obst et al, 2000;Oldenburg, 2004;Meister, 2009). Döll et al (2002), reported that in the case of non fungicide treatment, wheat from organic farming is more tolerant to Fusarium infection than wheat from conventional farming systems.…”
Section: Resultsmentioning
confidence: 99%
“…Organic cultivation is characterized by the omission of maize as previous crop, traditional tillage, and by selection of relatively Fusarium-resistant cultivars. Furthermore, the ban of plant protectants and other chemicals such as fungicides or growth regulators (retardants) which are applied in integrated cultivation could contribute to the relatively low Fusarium contamination (and thus of the low toxin contents) in organically cultivated cereals (Meier et al, 2000;Obst et al, 2000;Oldenburg, 2004;Meister, 2009). Döll et al (2002), reported that in the case of non fungicide treatment, wheat from organic farming is more tolerant to Fusarium infection than wheat from conventional farming systems.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies comparing trichothecene levels in conventional and organic grains are also contradictory (Hoogenboom et al. ; Edwards ,b, Meister ; Bernhoft et al. , ; Vidal et al.…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies have reported lower amounts of Fusarium and mycotoxin contamination in organic cereal production than in conventional production (Bernhoft et al, 2010;Edwards, 2009;Gottschalk et al, 2009;Meister, 2009). Pesticide use, high nitrogen application and cereal intense rotations in the conventional system have been hypothesised to cause these differences (Bernhoft et al, 2010;Edwards, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have shown lower or equal levels of Fusarium and mycotoxin contamination in organic cereal production than in conventional production (Bernhoft et al, 2010;Birzele et al, 2002;Edwards, 2009;Gottschalk et al, 2009;Meister, 2009). In the UK, Edwards (2009) observed lower levels of HT-2 and T-2 in organically produced wheat, but no difference in DON contamination.…”
Section: Introductionmentioning
confidence: 99%